A Prospective Intervention Study of Colonoscopy Reporting among Patients Screened or Surveilled for Colorectal Neoplasia - Daphnée Beaulieu; Myriam Martel; Alan Barkun (Canadian Journal of Gastroenterology)
BACKGROUND: The impact of modifying electronic colonoscopy reporting software for improving adherence to guidelines regarding quality standards documentation remains poorly characterized.